Development Development of Social Studies Teaching Materials Based on Local Potential in Cepu Region for Middle School Students in Blora - Nurita, Lilin (Jurnal Dialektika Pendidikan IPS, 2022)
The purpose of this study was to produce teaching materials in the form of modules based on the local potential of the Cepu area on the material "Population Economic Activities" and to determine the feasibility and effectiveness of teaching materials developed for 7th grade junior high school students in Blora. This type of research is Research and Development (R&D) research with ADDIE development procedures (Analysis, Design, Development, Implementation, Evaluation). The research design is one group pretest posttest. The research locations are in four locations, namely SMPN 5 Cepu, SMPN 1 Cepu, Islamic Middle School Cepu and SMPK St.Louis Cepu. The sample of this research is 99 students. Collecting research data using observation methods, instruments, tests, interviews, literature studies and documentation. The analytical technique used is descriptive qualitative analysis and inferential analysis. The feasibility of teaching materials is measured by testing the validity of design and material experts. While the effectiveness is measured from learning outcomes which are analyzed using the Paired Sample T-Test and categorized using N-Gain. The results of the study are (1) the Cepu area has local potential that is very relevant to social studies learning materials. The economic activities of the Cepu community which consist of production, distribution and consumption activities cannot be separated from local potentials, namely oil and gas and teak forests; (2) the module based on the local potential of the Cepu area "Very Appropriate" is used in social studies learning with the results of media expert validation 3.33 and material expert validation 3.58; (3) there is an increase in student learning outcomes in the aspect of knowledge, as evidenced by the average value of N-Gain in the quite effective category. Keywords: Module, Study, Local Potential